2005
DOI: 10.1021/la0468848
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Patterning of Flat Carbon Surfaces by Scanning Probe Lithography and Electrochemistry

Abstract: We report the formation of carbon surfaces patterned at the nanoscale with organic functionalities. Thin (<10 nm) films are covalently grafted to the surface via the electrochemical reduction of aryl diazonium salts. Areas of the film are removed with an AFM tip, and a second modifier is electrochemically grafted to the exposed surface. The pattern can incorporate different chemical functionalities, or alternatively topographical patterns can be assembled, where the same functionality is present throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 13 publications
0
84
0
Order By: Relevance
“…Proposed reaction mechanism for the reductive adsorption of aryl diazonium salts to electrode surfaces advantages. One example of the advantages of multilayers being formed from aryl diazonium salts is the nanoscale patterning of layers as demonstrated by Downard and coworkers [95]. In this procedure, an initial layer was deposited followed by specific regions being scratched away, in a process similar to nanoshaving [96], using an AFM tip.…”
Section: Aryl Diazonium Salt Modified Carbon Electrodesmentioning
confidence: 99%
“…Proposed reaction mechanism for the reductive adsorption of aryl diazonium salts to electrode surfaces advantages. One example of the advantages of multilayers being formed from aryl diazonium salts is the nanoscale patterning of layers as demonstrated by Downard and coworkers [95]. In this procedure, an initial layer was deposited followed by specific regions being scratched away, in a process similar to nanoshaving [96], using an AFM tip.…”
Section: Aryl Diazonium Salt Modified Carbon Electrodesmentioning
confidence: 99%
“…On the one hand, it has been used to evidence the difference of reactivity between graphene single and multilayers [20], to identify diamond surface terminations and measure the density of hydrogen atoms bonded to the surface [21] or to illustrate nanoscale patterning of carbon surface [22]. On the other hand, NBD was reported to modify the electrical properties of graphene field-effect transistors [23] or to help at covalent immobilization of organometallic model of enzyme onto carbon surface [24].…”
Section: Introductionmentioning
confidence: 99%
“…[56] Recently, Downard et al published the micro-and nanoscale patterning of carbon surfaces with different organic functionalities using soft lithography, AFM, and electrochemically assisted grafting. [57,58] Gooding et al, [59] and more recently BØlanger et al, [60] have reported another interesting method for the simultaneous bifunctionalisation of a GC electrode by differently substituted phenyl groups, achieved by electrochemical reduction from a solution containing a mixture of the corresponding diazonium salts. The major disadvantage of using electrochemical reduction of substituted aryl diazonium salts for surface modification is the low stability and availability of diazonium salts bearing suitable functional groups.…”
Section: Introductionmentioning
confidence: 99%